Variation in nutritional value of Grewia tenax fruits from different regions of Rajasthan, India - Rathore, Mala (Journal of Phytology, 2018)
In the present investigation, an attempt has been made to identify the variation in nutritional value of Grewia tenax fruits from different regions of Rajasthan, India. Fruits were collected from Jodhpur (Kailana, Bilara) and Barmer (Siwana) region and analyzed nutritionally. Maximum ash and vitamin C content was obtained in samples from Siwana (4.73% and 56.47% respectively). Maximum fat content (2.66 %) was obtained in samples from Bilara. Maximum sugar and protein content was obtained in samples from Kailana (35.51% and 8.4% respectively).. They are rich in vitamin C (39 mg/100gm) content. The fruits are also rich sources of minerals such as Ca (0.32±0.03 g/100g), K (1.26±0.31g/100 g) and Na (1.49±0.32 g/100g) than the cultivated crop plants. Trace elements such as Fe, Zn, Cu, Mn and Mg were also analyzed. These results of nutritional composition were compared with those collected from Bilara and Siwana area of Jodhpur region. Many medicinal applications of G. tenax viz. as remedy for colds and chest complaints have also been reported. Thus, the importance of G. tenax in the rural economy is highly significant.